Prognosis and recurrence pattern of patients with cervical carcinoma and pelvic lymph node metastasis - Shrestha, Eliza; Ying, Xiong; Li-Zhi, Liang; Min, Zheng; Luang-Hong, Wang; Peng-Fei, Deng; Ji-Hong, Liu (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aim: To investigate the prognostic risk factor(s) and pattern of disease relapse of patients with cervical carcinoma and pelvic node metastasis. Methods: One hundred twenty four cases of FIGOIB1~IIA cervical carcinoma with pelvic node metastasis treated from January 1991 to December 2001 were selected for this study. Prognosis and recurrence were retrospectively analyzed using the clinico-pathological data. Results: The overall 5 year survival and disease-free survival (DFS) was 63.3% and 61.4% respectively. Overall recurrence rate was 39.5% (49/124). Intra-pelvic relapse (25/41, 61.0%) was significantly more frequent than extra-pelvic relapse (13/41, 1.7%, P=0.008). Multivariate analysis identified involvement of common iliac node as independent prognostic factor (P=0.035). According to this factor, node-positive patients could be divided into low risk group (without common iliac node involvement, 104 cases) and high risk group (with common iliac node involvement, 20 cases). The DFS were 69.4% and 24.5% respectively, and the difference was significant (P=0.003). Intra-pelvic relapse was observed in 22.1% of low risk and 25.0% of high risk group respectively, the difference was not significant (P>0.05), however extra-pelvic relapse was seen in 7.7% of low risk and 40.0% of high risk group, and the difference was significant (P<0.001). Conclusions: Common iliac node involvement is the significant factor that influences the prognosis of patients with cervical carcinoma and pelvic node metastasis. According to this factor, survival and recurrence pattern differs significantly. These findings provide important reference for individualized modification and investigation of treatment mode. Keywords: Cervical neoplasms; lymph node metastasis; prognosis DOI: 10.3126/njog.v4i1.3327 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 19-24